2003
DOI: 10.1242/jcs.00289
|View full text |Cite
|
Sign up to set email alerts
|

Real-time analysis of clathrin-mediated endocytosis during cell migration

Abstract: . Real-time analysis of clathrin-mediated endocytosis during cell migration. J. Cell Sci. 116, 847-855.In both the online and print versions of this paper, in Materials and Methods, the construct pEGFP-dynamin2 was incorrectly identified as a human isoform. It is a rat isoform. AUTHOR CORRECTION IntroductionThe internalization of integral membrane proteins from the cell surface through receptor-mediated endocytosis occurs via clathrin-coated pits (Schmid, 1997;Takei and Haucke, 2001). Examples of molecules tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
164
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 47 publications
20
164
1
3
Order By: Relevance
“…The finding that CCPs per se are not specifically enriched at the leading edge is in line with the broad distribution of AP-2 observed in migrating ECV304 cells [49] and the non-polarized uptake of the bona fide CME cargo transferrin in migrating fibroblasts [50]. When looking more specifically at CCP dynamics in different cell regions, the number of disappearing CCPs per area was reported to be increased in the front region [48]. However, as this number was not normalized to the total, this difference might originate from the likewise increased total number of clathrin puncta.…”
Section: Excursion 1: Polarization Of the Endocytic Machinery During supporting
confidence: 68%
See 2 more Smart Citations
“…The finding that CCPs per se are not specifically enriched at the leading edge is in line with the broad distribution of AP-2 observed in migrating ECV304 cells [49] and the non-polarized uptake of the bona fide CME cargo transferrin in migrating fibroblasts [50]. When looking more specifically at CCP dynamics in different cell regions, the number of disappearing CCPs per area was reported to be increased in the front region [48]. However, as this number was not normalized to the total, this difference might originate from the likewise increased total number of clathrin puncta.…”
Section: Excursion 1: Polarization Of the Endocytic Machinery During supporting
confidence: 68%
“…When dividing migrating cells into a lagging, middle and leading region, Rappoport et al observed an enrichment of clathrin, dynamin2 and transferrin in the middle and front region versus the rear of the cell. However, there was no difference between middle and front region arguing for a rather weak polarization of the endocytic machinery in the direction of cell migration [48]. The finding that CCPs per se are not specifically enriched at the leading edge is in line with the broad distribution of AP-2 observed in migrating ECV304 cells [49] and the non-polarized uptake of the bona fide CME cargo transferrin in migrating fibroblasts [50].…”
Section: Excursion 1: Polarization Of the Endocytic Machinery During supporting
confidence: 54%
See 1 more Smart Citation
“…Dans la plupart des cellules, les puits recouverts de clathrine sont distribués de façon homogène et aléatoire à la membrane plasmique. Cependant, il n'en va pas de même au cours de la migration cellulaire, et nous avons confirmé des observations plus anciennes [7] montrant que les puits recouverts de clathrine s'accumulent préférentiellement à l'avant des cellules cancéreuses en migration ( Figure 2A). Cette distribution asymétrique des puits recouverts de clathrine est en soi remarquable et doit être mise en parallèle avec d'autres observations ayant éta-bli que les microtubules acétylés sont essentiellement dirigés vers l'avant des cellules en migration [8,9].…”
Section: An Allergic Response To Fight Against Venoms Liens D'intérêtunclassified
“…Nous avons donc mis au point un système L'excès de centrosomes contribue à une réduction de la taille du cerveau Les mutations identifiées chez des patients atteints de MCPH ont été incriminées dans la diminution du nombre de centrosomes fonctionnels dans la population des cellules souches neuronales (CSN) [5,6]. Notre équipe a récemment développé et caractérisé une lignée de souris chez laquelle l'amplification centrosomale est restreinte à la population des CSN [7]. Nous avons choisi de perturber la machinerie de duplication …”
Section: Des Puits Vers La Lumièreunclassified